Monetary policy in the Euro area: Lessons from the first years - Volker Clausen; Bernd Hayo (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
This paper investigates in a consistent semi-structural empirical framework three current issues of monetary policy in the euro area. First, regarding policy transmission we offer a three-stage procedure to combine the efficient estimation of economic structure prior to EMU with current ECB monetary policy. Second, we test whether the regime change leads – before or after – EMU to structural instability. Third, we investigate the stance of monetary policy in Europe. We compare a “counterfactual” ECB reaction function based on average interest rates prior to EMU with actual ECB policy. Furthermore, we compare actual ECB policy with interest rate projections using Bundesbank reaction functions and euroland data.
Keywords: E52; F41; 330; European Monetary Union; Monetary policy; Semi-structural modelling; Reaction function; Taylor rule; Transmission mechanism; Geldpolitik; Europäische Wirtschafts- und Währungsunion; Transmissionsmechanismus; Taylor-Regel; Schätzung